Reviews of Books (International review of mission, 1954)
Books Reviewed in this article: THE NATURE OF THE CHURCH: The Household of God. By Lesslie Newbigin. UNION IN SOUTH INDIA: Church of South India: The Movement towards Union. 1900 to 1947. By Bengt Sundkler. UNION IN SOUTH INDIA: What is this Church of South India? By Douglas Webster. EVANGELISM IN INDIA: Ways of Evangelism: Some Principles and Methods of Evangelism in India. Edited by Roland W. Scott. MUHAMMAD AND THE KORAN: Introduction to the Qur'an. By Richard Bell. A CHRISTIAN AND A GERMAN PROBLEM: Die Judenfrage, ein christliches und ein deutsches Problem: Vier Vorträge gehalten an der Deutschen Hochschule für Politik. By Paul Tillich. THE CHRISTIAN APPROACH TO THE JEWS: The Church and the Jewish People. Edited by Göte Hedenquist. THE MEANING OF REVIVAL: Revival: an Enquiry. By M. A. C. Warren. INTER-RACIAL CONCERN FOR KENYA: His Kingdom in Kenya. By Adelphoi. FALLACIES IN THE WAR FOR RIGHTEOUSNESS: Christianity, Diplomacy and War. By Herbert Butterfield. A DEFENCE OF THE STATE OF ISRAEL: End of an Exile. By James Parkes. A STUDY OF ORGANIZED DISRUPTION: Apostles of Discord. By Ralph Lord Roy. KACHIN SOCIAL STRUCTURE: Political Systems of Highland Burma: A Study of Kachin Social Structure. By E. R. Leach. NATIVES IN THE ECONOMY OF AFRICA': Os Nativos na Economia Africana. By Marcelo Caetano. IN PRISON IN CHUNGKING: With God in Red China. By F. Olin Stockwell. WORSHIP IN SCHOOLS AND COLLEGES: Worshipping Together. A service book for schools and colleges. Planned by a group of missionaries brought together by the International Committee on Christian Literature for Africa and compiled by Stanley H. Childs. London: Oxford University Press.